Implementasi Pendaftaran Pasien Rawat Inap Pada Rekam Medis Elektronik Di Rumah Sakit Tk III Bhayangkara Banjarmasin - Renaldy Renaldy; Nirma Yunita; Husin Husin (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2024)
The Implementation of Electronic Medical Record (EMR) Increases Work Efficiency in Medical Record Management. EMR enables faster and easier access to information, improving data integration between hospital management systems and other systems to reduce human error. This study aims to determine the implementation of inpatient registration in EMR at Bhayangkara TK III Hospital Banjarmasin. This research is qualitative with a descriptive approach, data collection through observation and interviews. The research subjects consisted of 3 people, namely the Head of the Medical Record Unit, the Head of the IT Unit, and the Inpatient Registration Officer. The results of this study indicate that the implementation of inpatient registration in terms of human resources has followed EMR training, there is a Standard Operating Procedure (SOP), and officers apply the SOP. The inpatient registration facilities meet the needs of officers, but there are still obstacles, namely errors in the SIMRS Khanza network during service hours.